Four- and five-photon upconversion lasing from rare earth elements under continuous-wave pump and room temperature - Jiang Bo; Hu Yuchan; Ren Linhao; Zhou Han; Shi Lei; Zhang Xinliang (Nanophotonics)
Benefited from abundant long-lived intermediate energy levels of rear earth elements, large anti-Stokes lasing can be realized by multi-photon upconversion processes, which does not demand rigorous phase match and ultrahigh pump power. Here, we have fabricated an Er-doped silica microsphere with an ultrahigh intrinsic quality factor of 1.2 × 108. By continuous-wave (CW) excitation at 1535 nm, four- and five-photon upconversion lasers are achieved simultaneously under room temperature, in which the lasing thresholds are estimated as 176 and 600 μW, respectively. Beside the ultralow thresholds, the microlaser also exhibits good stability of lasing intensity for practical applications. The four- and five-photon upconversion lasing from rare earth elements have not been separately demonstrated under CW pump and room temperature until this work. This demonstration provides a prospect to realizing high-performance short-wavelength laser by pumping low-energy photons.